Optimization of immunohistochemical detection of rat ESR2 proteins with well-validated monoclonal antibody PPZ0506. (1st March 2021) - Hattori, Yujiro; Ishii, Hirotaka; Higo, Shimpei; Otsuka, Mai; Kanaya, Moeko; Matsumoto, Keisuke; Ozawa, Mina; Ozawa, Hitoshi
Abstract: Although there are few well-validated antibodies against ESR2 proteins, a recent validation assessment identified a specific monoclonal antibody against human ESR2 proteins (PPZ0506). Furthermore, our previous study confirmed its cross-reactivity and specificity against rodent ESR2 proteins, enabling the determination of true ESR2 distribution profiles in rodents. Therefore, we aimed to determine optimal conditions for ESR2 detection by PPZ0506 immunostaining and analyze ESR2 distribution in rats. We evaluated several staining conditions using paraffin-embedded and frozen ovary sections. Immunohistochemical staining with PPZ0506 antibody required strong antigen retrieval and appropriate antibody dilution. Subsequent immunohistochemical analysis in multiple tissues under optimized conditions revealed that rat ESR2 proteins are expressed in a more localized manner than previously assumed. Our results suggest that previous immunohistochemical studies using inadequately validated antibodies against ESR2 proteins overestimated their distribution profiles. We expect that optimized immunohistochemical detection with PPZ0506 antibody can help researchers solve several conflicting problems in ESR2 research. Highlights: A well-validated anti-ESR2 antibody (PPZ0506) was recently identified. Immunohistochemical staining of rat ESR2 proteins with the antibody was optimized. The immunostaining required appropriate antigen retrieval and antibody dilution. ESR2 distribution in rat tissues was examined under the optimized conditions. The analysis revealed more localized ESR2 expression than previously assumed.